17β-estradiol/progesterone in a single, oral, softgel capsule (TX-001HR) significantly increased the number of vasomotor symptom-free days in the REPLENISH trial. Issue 12 (December 2020) - Kaunitz, Andrew M.; Bitner, Diana; Constantine, Ginger D.; Bernick, Brian; Graham, Shelli; Mirkin, Sebastian
Abstract: Objective: To examine responder rates and vasomotor symptom-free days with oral 17β-estradiol/progesterone (E2/P4; TX-001HR) versus placebo in the REPLENISH trial. Methods: REPLENISH (NCT01942668) was a phase 3, randomized, double-blind, placebo-controlled, multicenter trial, evaluating single, oral, softgel E2/P4 capsules in postmenopausal women (40-65 y) with a uterus and vasomotor symptoms (VMS). Women with moderate to severe hot flushes (≥7/d or ≥50/wk) were randomized (VMS substudy) to daily E2/P4 (mg/mg) of 1/100, 0.5/100, 0.5/50, 0.25/50, or placebo. Proportions of women with ≥50% or ≥75% reductions in moderate to severe VMS (responders), and those with no severe VMS as well as the weekly number of days without moderate to severe VMS with TX-001HR versus placebo were determined. Mixed model repeated measures was used to analyze data and Fisher exact test was employed to compare E2/P4 versus placebo. Results: Seven hundred twenty-six women were eligible for the VMS efficacy analysis (E2/P4 1/100 [ n = 141], 0.5/100 [ n = 149], 0.5/50 [ n = 147], 0.25/50 [ n = 154], or placebo [ n = 135]). Significantly more women treated with all E2/P4 doses versus placebo were ≥50% responders and ≥75% responders at weeks 4 and 12 ( P < 0.05) and also had significantly more days per week without moderate to severe VMS at week 12 (1.9-3.0 d for E2/P4 versus 1.3 d for placebo; P < 0.05). The proportion of women without severe hot flushes at week 12 was 43% to 56% for all E2/P4 doses versus 26% for placebo ( P ⩽ 0.01). Conclusions: Women treated with E2/P4 had a greater response to treatment with more VMS-free days than with placebo. The E2/P4 1/100 dose (Bijuva [E2 and P4] capsules) represents an oral treatment option for postmenopausal women with moderate to severe VMS and a uterus.